MICROSTRUCTURE AND MECHANICAL PROPERTIES BY ADDITION OF Zn AND TiH2 IN QUATERNARY Mg ALLOY FOAM - Lestari, Franciska Pramuji; Julhida, Fajar; Erryani, Aprilia; Kartika, Ika (LIPI Press, 2018)
In our current work, magnesium alloy foams with closed-cell were successfully fabricated by using space holder method, respectively.In this study, sintering process in powder metallurgy was chosen tofabricate quaternary porous Mg-Ca-Zn-TiH2 with addition NaCl as space holder and Zn as alloying. Effect of NaCl and Zn addition on porosity, phase formation and mechanical properties was observed. Sintering process was done in constant temperature sintering 600°C and holding time for 5 hours under Argon atmosphere. The porosity was evaluate with Archimedes method, while the porous structure of the resulted alloys was examined using Scanning Electron Microscope (SEM), and the phase formation was characterized by X-ray diffraction (XRD) analysis. Mechanical properties were examined using compression testing. From this study, decreasing TiH2 and increasing of Zn content in Mg alloy will increase the compressive strength because of reducing the porosity. Furthermore, according to the results, the porous Mg alloy could be considered one of the most promising scaffold materials for hard tissue regeneration.